PROVIDING PERSONAL RIGHTS AND FREEDOMS OF DEFENDANDT IN CASES HE DOES NOT KNOW THE LANGUAGE OF THE JUDICIAL PROCEEDINGS AND AGREEMENTS ON CONFESSIONS (Academicia Globe: Inderscience Research, 2022)
The article examines the existing problems in ensuring the rights and freedoms of the individual in cases where the court does not know the language of the proceedings and the plea agreement is concluded, and offers suggestions for their elimination.